Efficacy of herbal extracts and closantel against fenbendazole-resistant Haemonchus contortus. Issue 5 (24th July 2018) - Dixit, A.K.; Das, G.; Dixit, P.; Sharma, R.L.
Abstract: This study assessed the efficacy of closantel vis-à-vis herbal extracts with known anti-parasitic properties, against fenbendazole-resistant nematodes in goats maintained under a semi-intensive system of management at the University goat farm, Jabalpur. Fifty goats were randomly assigned to five groups, each comprising 10 animals, irrespective of their breed, age and sex. Each animal in Group I, II and III was orally administered with aqueous leaf extracts of neem ( Azadirachta indica ) at 1 g/kg body weight, sitaphal ( Annona squamosa ) at 1.5 g/kg body weight and tobacco ( Nicotiana tabacum ) at 1 g/kg body weight, respectively, whereas Group IV was an untreated control group. Each animal in Group V was orally treated with closantel at 10 mg/kg body weight. During the course of the study, all animals were maintained under an identical semi-intensive system of management. Compared to the untreated control group (Group IV), there was no conspicuous reduction in post-treatment (day 10) faecal egg counts (FEC) in animals administered with the herbal extracts (Groups I, II and III), which is suggestive of poor anti-parasitic activity. However, using the faecal egg count reduction test (FECRT), the overall efficacy of closantel was recorded as 95.64%. This supports the rotational use of closantel as a preferred choice over the benzimidazole group of anthelmintics and/or herbal extracts to meet the acute challenge of in situ development of drug-resistant gastrointestinal nematodes, especially Haemonchus contortus .